1976
DOI: 10.1128/aac.10.2.234
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyquinolines Inhibit Ribonucleic Acid-Dependent Deoxyribonucleic Acid Polymerase and Inactivate Rous Sarcoma Virus and Herpes Simplex Virus

Abstract: 8-Hydroxyquinoline and several of its derivatives inactivate the transforming ability of Rous sarcoma virus and inhibit its ribonucleic acid-dependent deoxyribonucleic acid polymerase activity. The copper complex of these metal-binding ligands is as active as the free ligand. The activity of the 8-hydroxyquinolines is approximately 50-fold more effective than another group of metal-binding compounds that we have tested, the thiosemicarbazones. In contrast to the potency of the 8-hydroxyquinolines to inactivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…In Alzheimer and Parkinson disease treatment, CQ binds to copper, thus decreasing copper concentration accumulated in brain tissues (21). CQ is also able to inhibit RNA-dependent DNA polymerase and inactivates Rous sarcoma virus and Herpes simplex virus by forming a complex with copper (42). By careful analysis, we can find that one of the key features in the physiochemical properties of CQ in the therapeutic activity is that CQ possesses the capacity to chelate divalent metal ions such as zinc and copper.…”
Section: Discussionmentioning
confidence: 99%
“…In Alzheimer and Parkinson disease treatment, CQ binds to copper, thus decreasing copper concentration accumulated in brain tissues (21). CQ is also able to inhibit RNA-dependent DNA polymerase and inactivates Rous sarcoma virus and Herpes simplex virus by forming a complex with copper (42). By careful analysis, we can find that one of the key features in the physiochemical properties of CQ in the therapeutic activity is that CQ possesses the capacity to chelate divalent metal ions such as zinc and copper.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of NGO2054 may further fortify the cell envelope against larger molecules, as the mutant grew to an OD 600 of 0.079, while the WT did not grow at all. The copper chelator 5,7-dichloro-8-hydroxyquinoline is has been shown to inhibit DNA polymerase activity and inhibit Rous sarcoma virus and herpes simplex virus 1 (85). Nordihydroguaiaretic acid and benserazide were both detrimental to the growth of the Δngo2054 mutant (blue bars).…”
Section: Figmentioning
confidence: 99%
“…It was shown that 8 hydroxyquinoline and some of its derivatives deacti vate the transforming ability of the Rous sarcoma virus and inhibit the RNA dependent DNA polymerase of the virus. The simple herpes virus (Herpes viruses sim plex) also is inactivated by 8 hydroxyquinolines and their copper complexes [6]. Anti leishmanial activity of the various 8 hydroxyquinolines containing an izoxazoline fragment at the C7 atom was recently dis Abbreviations: 15C5, 15 crown 5; TBAH, tetrabutylammonium hydrogen sulfate; ClogP, calculated logarithm of the distribution coefficient of the compound between octane 1 and water [11].…”
Section: Introductionmentioning
confidence: 99%
“…1 covered [7]. The high antimicrobial and antifungal activity of 8 hydroxyquinolines is related to their chelating ability [3,6,8] that requires the presence of a free OH group in the position 8 of the quinoline nucleus. Nevertheless, 8 O substituted hydroxyquino lines were found, which were highly effective antimi crobials [9].…”
Section: Introductionmentioning
confidence: 99%